Spatial Damped Anomaly Persistence (SDAP) Forecasts of Sea Ice Presence in the Arctic between 1999 and 2020 - Niraula, Bimochan; Goessling, Helge (Zenodo, 2021)
Spatial Damped Anomaly Persistence Forecasts of Sea Ice Presence in the Arctic between 1999 and 2020. Each netcdf file corresponds to a single initialisation, done at the start of the stated month, and the forecasts for the following 120 days, both probabilistic (SDAP) and deterministic (SAP) forecasts. The forecasts were derived using OSI SAF sea-ice concentration records (OSI SAF 450 and 430b) and follow the resolution of that dataset (25 km EASE-2 grid). Further details regarding the forecasting method and the results can be found in Niraula et Goessling, 2021 (in review). Please note that while the filenames say "DampedForecast", each file contains both Damped or Deterministic forecasts associated with the date. We acknowledge the financial support by the Federal Ministry of Education and Research of Germany in the framework of SSIP (grant 01LN1701A).